The Causal Relationship of the Feature Personality Traits Following Mediation Therapy Perceived Social Support in Female Cancer Patients - Maryam Mardani; Manijeh Firoozi; Tina Vosoughi (روانشناسی بالینی و شخصیت)
Introduction: Treatment adherence is a critical issue in both physical and mental health, as it plays a vital role in saving the lives of many individuals. The present study aimed to investigate the causal relationship between personality traits and treatment adherence, as well as the mediating role of social support in female cancer patients.Method: The research method employed was descriptive, and the research design utilized correlational structural equation modeling (SEM). A total of 310 women with cancer in Ahvaz were selected during the winter of 2023 using convenience sampling. The instruments utilized in this study included the Treatment Adherence Questionnaires (Seyedfatemi et al., 2018), the NEO Personality Inventory (Costa and McCrae, 1992), and the Perceived Social Support Scale (Zimt et al., 1988). SPSS software was utilized for descriptive data analysis, while AMOS software was employed to assess the model. Direct relationships were calculated using AMOS software, while indirect relationships were assessed through the bootstrap method in AMOS. The analysis reported absolute fit, relative or incremental fit, and adjusted fit indices. Structural equation modeling analyses confirmed that the proposed model was appropriate.Results: The results also indicated that personality traits and their subscales—neuroticism, extraversion, openness to experience, agreeableness, and conscientiousness—affected treatment adherence through the mediation of social support.Discussion and Conclusion: Given the critical issue of treatment adherence, it is essential to focus on related and influential factors, such as personality traits and social support. Health and mental health officials, as well as policymakers, should prioritize these variables to enhance treatment adherence.